Disaffected democracies : what's troubling the trilateral countries? - Pharr, Susan J.; Putnam, Robert D. (Princeton, New Jersey : Princeton University Press, 2000)
It is notable that as democracy replaces other forms of governing throughout the world, citizens of the most established and prosperous democracies increasingly report dissatisfaction and frustration with their governments. This volume examines why this is so.
Introduction : What's troubling the trilateral democracies? / Robert D. Putnam, Susan J. Pharr, and Russell J. Dalton -- The public trust / Russell Hardin -- Confidence in public institutions : faith, culture, or performance? / Kenneth Newton and Pippa Norris -- Distrust of government : explaining American exceptionalism / Anthony King -- Interdependence and democratic legitimation / Fritz W. Scharpf -- Confidence, trust, international relations, and lessons from smaller democracies / Peter Katzenstein -- The economics of civic trust / Alberto Alesina and Romain Wacziarg -- Officials' misconduct and public distrust : Japan and the trilateral democracies / Susan J. Pharr -- Social capital, beliefs in government, and political corruption / Donatella della Porta -- The impact of television on civic malaise / Pippa Norris -- Value change and democracy / Russell J. Dalton -- Mad cows and social activists : contentious politics in the trilateral democracies / Sidney Tarrow -- Political mistrust and party dealignment in Japan / Hideo Ōtake.
Includes bibliographical references (pages 319-346) and index.
Print version record.
JSTOR
Keywords: Honʼyaku iin shachū; Universidad Sergio Arboleda; Democracy; Europe -- Politics and government; Japan -- Politics and government; United States -- Politics and government; Democracy; Démocratie.; Europe -- Politique et gouvernement; Japon -- Politique et gouvernement; États-Unis -- Politique et gouvernement; democracy; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Democracy; Politics and government; Europe; Japan; United States; Demokratie; Legitimität; Parlamentarismus; Politische Krise; Politisches System; Politikverdrossenheit; Westeuropa; Westliche Welt; Japan; USA; Democratie; Politiek vertrouwen; Publieke opinie; Aufsatzsammlung